Better climate action through the right knowledge? Development and validation of an item-response-theory scale measuring climate effectiveness knowledge - Simon, Clara Elisa; Merten, Martin Julian (Frontiers in Psychology, 2024)
Knowledge about the relative environmental impact and climate-protective potential of different actions (effectiveness knowledge) is important for successful sustainable action. However, there is currently no scale for measuring effectiveness knowledge that meets psychometric quality criteria. We developed a new scale consisting of 16 ranking and choice tasks and tested it on a convenience sample of 278 people from Germany in an online study. The final scale version achieved a reliability of rel = 0.655. This is significantly higher than the reliability of 0.329 achieved by an established knowledge scale used for comparison. Inter-correlation of both scales was moderate to strong, but the new scale is able to explain 3% additional variance in high-impact pro-environmental behavior when controlling for environmental attitude, whereas the established scale is not explaining any additional variance, indicating incremental validity of our scale. We conclude that it is possible to use ranking tasks to measure effectiveness knowledge more reliably in a test-efficient way and provide a set of items which are usable in the contemporary German context.